The loveliest chocolate shop in paris eaudiobook - Colgan, Jenny (Tantor Media, 2018)
It's true that Anna Trent is a supervisor in a chocolate factory . . . but that doesn't necessarily mean she knows how to make chocolate. And when a fateful accident gives her the opportunity to work at Paris's elite chocolatier Le Chapeau Chocolat, Anna expects to be outed as a fraud. After all, there is a world of difference between chalky, mass-produced English chocolate and the gourmet confections Anna's new boss creates. But with a bit of luck and a lot of patience, Anna might learn that the sweetest things in life are always worth working for. Hopeful, laugh-out-loud funny, and irresistibly addictive, The Loveliest Chocolate Shop in Paris is a novel worth savoring.